Community Quality-of-Life Indicators
X, 332 p.
Keywords: This book is second in a series covering best practices in community quality-of-life (QOL) indicators. The first volume in this series is a compilation of cases of best work in community indicators research. This second volume continues to build on the goal of the series and includes eleven cases (chapters). The cases in both volumes describe communities that have launched their own community indicators programs. Elements that are included in the descriptions are the history of the community indicators work within the target region, the planning of community indicators, the actual indicators that were selected, the data collection process, the reporting of the results, and the use of the indicators to guide community development decisions and public policy. This series will be of great value to community planners, urban planners, city planners, regional planners, quality-of-life researchers and researchers in public administration.